Analisis Dampak Perilaku Verbal Bullying Terhadap Kecerdasan Interpersonal Siswa Kelas IV SDN 1 Winong - Ika Novitasari; Fikriyah Fikriyah; Susilawati Susilawati (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The rise of verbal bullying behavior that occurs among students can have an impact on students' interpersonal intelligence. The purpose of this research is to find out 1) the form of verbal bullying that occurs against students, 2) find out the impact of verbal bullying behavior on students' interpersonal intelligence, and 3) find out how teachers deal with verbal bullying behavior. The approach used in this research is a qualitative approach with descriptive methods. The subjects of this research were victims of verbal bullying, perpetrators of verbal bullying and teachers. This research uses data collection techniques in the form of observation and interviews. The results of the research show that the form of verbal bullying that occurs is insulting, cursing and calling students, this is done by students unintentionally or just jokingly. The impact of verbal bullying on interpersonal intelligence makes students tend to become shy and lack self-confidence, this has an impact on students' ability to communicate, adapt and collaborate. Teachers overcome verbal bullying behavior by detecting bullying, providing support to victims of verbal bullying which has an impact on interpersonal intelligence, providing socialization regarding bullying and providing strict sanctions.